1881 Ill. Laws 73, §§ 1, 4 - (:unkn) unknown (General Publisher, 1881)
Prohibited the possession, selling, loaning, or hiring for barter of a slungshot or metallic knuckles or other deadly weapon. Punishable as a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION